IMPLEMENTATION OF BANK RAKYAT INDONESIA (BRI) SUPERVISION SYSTEM IN AN EFFORT TO PREVENT FRAUND IN BANKING SERVICE SYSTEM - Dedi Heryanto, Siti Robiati; Bastomi, Dwi Masria; Amran Muslimin, Zikrillah; Heri, M. Farhan Arrafi; Dadang Rahman, M. Ripaldy; Mahidin, Nurhayati; Imronniansyah, Jesica Natania (CV. Era Digital Nusantara, 2023)
It is important for Bank BRI to implement an effective fraud prevention control system in the banking service system. The purpose of this article is to analyze how Bank BRI implements a control system to prevent fraud from occurring in the banking service system. In addition, this study aims to determine the factors that hinder the implementation of the BRI control system. The research method uses a descriptive approach by gathering information from secondary sources such as related literature, bank regulations and financial reports. The results of this study indicate that BRI Bank implements various steps in the control system, including event monitoring, information security, training and awareness raising, as well as internal and external audits. However, this study also identified several factors that complicate the implementation of BRI's control system. These factors include limited resources such as budgets and personnel, the technological complexity of modern banking systems, and compliance with established regulations and policies. To increase the effectiveness of the control system, Bank BRI must overcome these obstacles by allocating adequate human resources, developing capabilities to respond to technological developments, and increasing compliance with banking laws. It is hoped that BRI's control system can work more effectively to prevent fraud and maintain customer trust in the banking services provided